Labor relations in the public sector - Kearney, Richard C.; Mareschal, Patrice M. (Public administration and public policy, 2014)
"Since publication of the fourth edition of Labor Relations in the Public Sector, public sector unions have encountered strong headwinds in many parts of the U.S. Membership is falling in some jurisdictions, public opinion has shifted against the unions, and political forces are leaning against them. Retaining the structure that made the previous editions so popular, this fifth edition incorporates a complete round of updates, particularly sections on recent trends in membership figures, new legislation, and new politics as they influence bargaining rights. What's New in the Fifth Edition: up to date examination and analysis of public sector labor relations and collective bargaining; important changes in the public labor relations and unionization landscape; updated analysis of the financial and human resource outcomes of collective bargaining in the public sector; collective bargaining institutions and processes in government. Completely updated in terms of the scholarly and professional literature and relevant events, the new edition identifies and explains the implications of the new collective bargaining environment, including financial and human resource management issues and outcomes. As in previous editions, collective bargaining and labor relations are addressed at all levels of government, with comparisons to the private and nonprofit sectors. Designed to be classroom friendly, it includes discussions of the most recent literature and case studies as well as end-of-chapter assignments and quizzes. Practical tips and advice are offered for those engaged in collective bargaining and labor relations"--Publisher description